Ancient Egypt : Civilizations of the Nile valley from pharaohs to farmers - Ricart, Joan; Ribot, Susana (UK : Parragon Book Ltd, 2014)
Presents one of history's most remarkable civilizations. Explores how ancient Egyptian society was organized, everyday life, religion, mythology, art, and more. Includes over 250 gorgeous photographs of art, artefacts and architecture, plus striking 3D illustrations
Keywords: Ancient civilizations -- Non-fiction; History of medicine -- Non-fiction